Implementasi Load Balancing Web Server Menggunakan Metode LVS-NAT - Jefry Alvonsius Rabu; Joko Purwadi; Willy Sudiarto Raharjo (Jurnal Informatika, 2013)
Web server plays a vital role on serving requests from clients. As Internet users grows so fast, the request number increases significantly, thus reducing the overall performance of the web server. One solution is to implement a load balancing system.In this paper, we implement load balancing with Linux Virtual Server to distribute the load to several machines within a cluster. We compared Round Robbin and Least Connection algorithm. The study reveals that load balancing using LVS-NAT can double the throughput output compared to single web server, but less significant on response time and CPU utilization. Implementing LVS-NAT using round robbin algorithm is more robust in optimizing the throughput, CPU utilization, and response time compared to least connection.